Locally advanced squamous cell cervical cancer in a patient with septate uterus - Yavas, Guler; Yavas, Cagdas; Inan, Gokcen (Journal of Contemporary Brachytherapy, 2017)
A 33-year-old premenopausal multiparous woman with the history of septate uterus was referred to the hospital with menorrhagia and inter-menstrual bleeding occurring for the last 6 months. Work-up revealed a stage IIB cervical cancer. The patient underwent curative chemo/radiotherapy. The patient’s septate uterus presented several difficulties during application. Brachytherapy was applied using standard computed tomography-compatible tandem and ovoids. The high-risk clinical target volume (HR-CTV), intermediate risk CTV, and organs at risk were contoured according to the Groupe Européen de Curiethérapie – European Society for Radiology and Oncology (GEC-ESTRO) guidelines. Treatment was performed via 3-dimensional high-dose-rate technique with 192Ir, with brachytherapy dose of 28 Gy in 4 fractions/7 Gy each, prescribed to the HR-CTV. Treatment was well tolerated with manageable acute toxicities. To the best of our knowledge, the current case is the second case of septate uterus with locally advanced cervical carcinoma. Due to the lack of guidelines about brachytherapy applications in patients with uterine anomaly and owing to the anatomical anomaly, brachytherapy application is challenging in this patients population.